Innovation and Startup Acquisition - Marc Bourreau; Axel Gautier (CESifo GmbH, 2024)
In this paper, we consider two platforms that compete for the development of a new product to integrate into their ecosystems. The new product can be developed either inhouse by the platforms or by an independent startup active only in the technology market. The presence of the startup affects the platforms' R&D efforts through an insurance effect, which reduces the cost of failure in innovation, and a competition effect, which diminishes the returns to innovation. The magnitude of these effects depends on the attitude of the competition authorities towards the acquisition of the startup by one of the platforms. We show that allowing acquisitions stimulates platform innovation, but at the cost of a more concentrated market structure. We also compare the funding of the startup by independent venture capitalists or by the platforms themselves, and investigate how the merger regime influences the direction of the startup's innovation.
Keywords: D43; G34; K21; L40; L86; 330; innovation; startup acquisitions; mergers; digital; big tech; competition policy